An Integrated Approach with Permutation Entropy Measure and Conventional Tests for Study on Stock Market Efficiency - Vu, Loan Thi; Nguyen, Anh Van; Dao, Quynh Nhu; Do, Ha Minh; Doan, Ha Thị Thuy (Journal of Ecohumanism, 2024)
Countries globally strive to create efficient stock markets to stimulate economic growth and encourage more investors. This paper deals with testing the weak form of the Efficient Market Hypothesis (EMH) using daily data across 57 global stock markets spanning from 2013 to 2023. Moreover, the study focuses on employing the combination of the Permutation Entropy measure to compute the weak form efficiency degree and several conventional tests to obtain a sufficient evaluation of the market efficiency in the sample. The traditional test results provide inconsistent conclusions on the weak form efficiency as the data series are non-normal distributed but follow a random walk pattern. However, combined with the high Permutation entropy scores estimated for the sample, it is concluded that all 57 markets are weak-form efficient. Furthermore, despite some exceptions, the developed markets tend to display the highest degrees of efficiency, followed by emerging markets, while frontier markets show the weakest efficiency.